2021
DOI: 10.1186/s12887-021-02708-x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of persistent overweight on perceptual-motor proficiency of primary school children: the North-West CHILD longitudinal study

Abstract: Background Overweight can be a precursor of poor motor execution, negatively impacting the overall development of school-aged children on various levels. This study determined the long-term influences of overweight on perceptual-motor proficiency (PMP) of primary school children in the North-West Province of South Africa. Methods The study, which included 381 participants, formed part of the NW-CHILD longitudinal study from Grade 1 (6.86 years, ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Most regional studies in preschool children (0–6 years) were conducted in rural areas (68 %), while a similar proportion of studies among school-age children were from rural and urban areas. Race and ethnicity of the study participants were not always reported, but only two studies in children from one race were included in this review ( 19 , 20 ) . National studies and studies with a large sample size generally included children from all race groups.…”
Section: Resultsmentioning
confidence: 99%
“…Most regional studies in preschool children (0–6 years) were conducted in rural areas (68 %), while a similar proportion of studies among school-age children were from rural and urban areas. Race and ethnicity of the study participants were not always reported, but only two studies in children from one race were included in this review ( 19 , 20 ) . National studies and studies with a large sample size generally included children from all race groups.…”
Section: Resultsmentioning
confidence: 99%
“…It was not surprising to find that overweight children performed worse than their non-overweight peers in all the tested motor skill categories (except for flexibility), in line with the literature [ 48 , 49 ]. Overweight children are known to show less development in their motor skills [ 50 ]. It was, therefore, surprising to see that the change in the tested motor skills in overweight children did not significantly differ from that in their non-overweight peers in any test item other than the standing long jump.…”
Section: Discussionmentioning
confidence: 99%
“…In the North West Province, a longitudinal study of 6-9 year old school children reported an overall increase from 12.5% at baseline to 16.7% prevalence of overweight/obesity over a 3-years period [16]. In the North-West Province of South Africa (SA), a recent study by de Waal and Pienaar [17] also revealed a prevalence of 9.97% among children of persistent overweight/obesity over a longitudinal period of 7 school years. This was also associated with poorer and deteriorating weight bearing motor skills and balancing skills in such children, which again can negatively influence healthy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Poor motor competency at a young age is furthermore associated with behavior that is conducive to obesity [23][24][25][26][27] and strongly influences healthy behavior. Therefore, a better understanding of this association to the obesity healthcare challenge is still needed [17]. Young children are still at an optimal age for motor skill development, thus preventing a decrease in motor coordination over time that may add to health challenges [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation